Dichlorophosphoranides Stabilized by Formamidinium Substituents. (13th February 2020) - Marchenko, Anatoliy; Koidan, Georgyi; Hurieva, Anastasiya; Rusanov, Eduard; Rozhenko, Alexander B.; Kostyuk, Aleksandr
Abstract : Dichlorophosphoranides featuring N, N -dimethyl- N ′-arylformamidine substituents were isolated as individual compounds. Dichlorophosphoranide 9 was prepared by the multicomponent reaction of C -trimethylsilyl- N, N -dimethyl- N ′-phenylformamidine and N, N -dimethyl- N ′-phenylformamidine with phosphorus trichloride. Its molecular structure derived from a single-crystal X-ray diffraction was compared to the analogous dibromophosphoranide prepared previously by us by the reaction of phosphorus tribromide with N, N -dimethyl- N ′-phenylformamidine. It was shown that a chlorophosphine featuring two N, N -dimethyl- N ′-mesitylformamidine substituents reacted with hydrogen chloride to form dichlorophosphoranide 11 . Its molecular structure was also determined by X-ray analysis and compared with that of closely related dichlorophosphoranide C .